Interactions between ocean carriers' operations and shippers' supply chain - Lee, Shi Ming. (2009)
Changes in the world such as globalization have modified the ways in which the shippers (firms) operate and increased the complexity of supply chains. Hence, it is important that shippers understand the factors that affect their supply chain performance. Firstly, this report will discuss about the factors affecting the supply chain performance, as well as the tradeoffs between these factors, so as to facilitate their decisions on their operating strategies. Research findings have revealed that to compete effectively and to improve their supply chain performance, more shippers are increasingly forming strategic partnerships with other supply chain members such as the suppliers and transport operators. This observation is further affirmed and explained by the survey and interview findings with industry professionals. This report will provide insights on supply chain partnerships and how these partnerships help shippers improve their supply chain performance, as well as how it improves their other supply chain strategies. A case study on IKEA is also included in this report to further illustrate on how supply chain partnerships and other supply chain strategies can help to improve the supply chain performance of IKEA.